2015
DOI: 10.1111/jon.12262
|View full text |Cite
|
Sign up to set email alerts
|

MRI Texture Analysis Reveals Deep Gray Nuclei Damage in Amyotrophic Lateral Sclerosis

Abstract: TA of T1 weighted images revealed DGN alterations in patients with ALS, namely in the thalami and caudate nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…This hypothesis is supported by a previous texture-based study in patients with a related neurodegenerative disorder, namely amyotrophic lateral sclerosis, that identified prominent texture abnormalities earlier than true volumetric reduction. 27 Also in line with these findings, some previous volumetric studies in FA failed to identify bulbar atrophy, 17 and others actually found it, 15 but it was restricted to the dorsal part of the structure in such a way that it would be difficult to explain our consistent texture modifications. Therefore, we opted not to include volumetric measurements of the medulla as a covariate in our statistical approach to compare groups.…”
Section: Discussionsupporting
confidence: 69%
“…This hypothesis is supported by a previous texture-based study in patients with a related neurodegenerative disorder, namely amyotrophic lateral sclerosis, that identified prominent texture abnormalities earlier than true volumetric reduction. 27 Also in line with these findings, some previous volumetric studies in FA failed to identify bulbar atrophy, 17 and others actually found it, 15 but it was restricted to the dorsal part of the structure in such a way that it would be difficult to explain our consistent texture modifications. Therefore, we opted not to include volumetric measurements of the medulla as a covariate in our statistical approach to compare groups.…”
Section: Discussionsupporting
confidence: 69%
“…Diffusion MRI studies in ALS consistently report markers of reduced thalamic cellular integrity 28 29. Thalamic abnormalities extend beyond conventional grey matter and diffusion change to altered functional connectivity,28 increased iron deposition,30 altered metabolism,31 decreased texture features,32 altered cerebral blood flow,33 reduced motor task-related activation34 and increased microglial activation 35. Thus, despite the variability of detectable grey matter atrophy, thalamic abnormalities are a very robust finding consistent across a wider range of neuroimaging modalities (table 4).…”
Section: Discussionmentioning
confidence: 93%
“…A novel three-dimensional (3D) voxel-wise texture analysis method also revealed the spatial pattern of pathology involving the medial temporal lobes in Alzheimer's disease in a hypothesis-free study (Maani, Yang, & Kalra, 2015). In ALS, texture changes have been observed in the CST and the deep gray nuclei (Albuquerque et al, 2016;Maani, Yang, Emery, & Kalra, 2016). However, the pathological substrates that underlie texture changes have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%